Robustness test method for intelligent electronic device - Haitao JIANG; Bin LI; Xiang WANG; Jinming CHEN; Yajuan GUO (Dianxin kexue)
To detect the robustness of communication module of intelligent electronic devices（IED）in smart station,a device robustness test method was presented based on abnormal messages,and a robustness testing system was achieved.Some devices were selected for robustness test experiment to verify the rationality and feasibility.Results show that the method can effectively detect the robustness of devices and locate the abnormal messages which cause devices' failure.